European Business: Corporate and Social Values - Segreto, Luciano; Segreto, Luciano; Bonin, Hubert (Peter Lang, 2011)
This book investigates the adaptation of companies to the trend towards Europeanisation, through the renewal of their business values, their corporate culture, their portfolio of skills and their transnationalisation. It also considers the spillover effects in terms of knowledge management, accountability and commercial opportunities. The examination of case studies involving several different European countries and corporations leads to stimulating arguments about the steady building of a European culture of management, fuelled by local experiences and cross-over corporate cultures. The writers in the volume consider how individual managers contribute to the outline of a European business culture, taking advantage of new methods of management and the converging mobilisation of human resources. Another important issue examined in the book is that of brands, which have to be managed according to their perceptions in different European countries.